2017
DOI: 10.1038/s41598-017-10022-9
|View full text |Cite
|
Sign up to set email alerts
|

Activation-tagging in indica rice identifies a novel transcription factor subunit, NF-YC13 associated with salt tolerance

Abstract: Nuclear factor Y (NF-Y) is a heterotrimeric transcription factor with three distinct NF-YA, NF-YB and NF-YC subunits. It plays important roles in plant growth, development and stress responses. We have reported earlier on development of gain-of-function mutants in an indica rice cultivar, BPT-5204. Now, we screened 927 seeds from 70 Ac/Ds plants for salinity tolerance and identified one activation-tagged salt tolerant DS plant (DS-16, T3 generation) that showed enhanced expression of a novel ‘histone-like tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 89 publications
1
30
0
Order By: Relevance
“…They have been also found to be involved in physiological processes, for instance, the regulation of endoplasmic reticulum (ER) stress [ 8,32], photosynthesis [33][34][35] and photomorphogenesis. In addition, some NF-Y genes also involve in the response to abiotic stresses [ 18,30,[36][37][38][39][40][41][42][43][44][45][46][47]. In leguminous plants, NF-Ys haven been suggested as important regulators of organogenesis and development of symbiotic root nodules [ 18,48] .…”
Section: Introductionmentioning
confidence: 99%
“…They have been also found to be involved in physiological processes, for instance, the regulation of endoplasmic reticulum (ER) stress [ 8,32], photosynthesis [33][34][35] and photomorphogenesis. In addition, some NF-Y genes also involve in the response to abiotic stresses [ 18,30,[36][37][38][39][40][41][42][43][44][45][46][47]. In leguminous plants, NF-Ys haven been suggested as important regulators of organogenesis and development of symbiotic root nodules [ 18,48] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it requires very few primary transformants to obtain a high frequency of transposition events. The rice OsNF‐YC13 transcription factor subunit, identified using Ac / Ds activation system, revealed significant tolerance against salinity stress (Manimaran et al, ). In rice, the Ribosomal Protein Large ( RPL ) subunit genes , RPL 6 and RPL 23A, were found to be upregulated in activation‐tagged lines.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of 70 Ac/Ds rice mutants for salinity tolerance identified one activation-tagged salt tolerant DS plant (DS-16, T3 generation), which showed enhanced expression of a gene encoding the NF-YC subunit, named OsNF-YC13 . The authors identified it as a possible salt stress tolerance gene ( Manimaran et al, 2017 ). In transgenic rice plants, overexpression of a NF-YC gene from Bermuda grass, CdtNF-YC1 , conferred tolerance to drought and salinity ( Chen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%